INTENSIFIKASI DAN EKSTENSIFIKASI PENERIMAAN PAJAK DAERAH DALAM MENUNJANG PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN NAGAN RAYA - Alisman Alisman; Irwan Suharmi; Fitri Nurhayani (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2018)
The  purpose of this study is to find out how much intensification and extensification of local tax revenues in supporting local revenue (PAD) in the district at Nagan Raya. The model used descriptive qualitative is to see the extensification and intensification of local tax revenues in supporting the original revenue (PAD) areas in Nagan Raya district from 2008-2017. The results of this study indicate that local taxes have potentials that have not been explored by the government in this case BPKD that has the potential to be developed that is restaurant tax and hotel tax then calculations made to the actual potential in know that local taxes have great potential, because the target in set the government still below the potential that matches the actual conditions. PAD’s original source of income in Nagan raya district is the district’s revenue and expenditure budget APBK. PAD’s original regional income is an important benchmark to determining the level of regional capacity in implementing regional autonomy in a real and responsible manner. The objects of original PAD regional income that are already running are supported by improvements or existing qanuns. Taxintensification and extensification in Nagan Raya regency is measured by the amount of income, real data collection and through good revenue capacity. The Nagan Raya district government in tax intensification needs to provide extension agents to improve taxpayers compliance by the community will increase the original income because the more obedient people who pay taxes, the better the original income of the PAD  will increase. Keywords : intensification and extensification of local tax revenue and local revenue